(untitled) (Journal of Computational Mathematics, 2021)
A class of exponentially fitted nonequidistant extrapolation methods based on an L-stable linear single-step formula are studied. Theorems about the extrapolation coefficients are given. These methods keep good numerical stability "quasi-L-stability", while raising the accuracy of the original formula.